Insights into the genetic foundation of aggression in Papio and the evolution of two length-polymorphisms in the promoter regions of serotonin-related genes (5-HTTLPR and MAOALPR) in Papionini. Issue 1 (December 2016) - Kalbitzer, Urs; Roos, Christian; Kopp, Gisela; Butynski, Thomas; Knauf, Sascha; Zinner, Dietmar; Fischer, Julia
Abstract Background Aggressive behaviors are an integral part of competitive interactions. There is considerable variation in aggressiveness among individuals both within and among species. Aggressiveness is a quantitative trait that is highly heritable. In modern humans and macaques (Macaca spp.), variation in aggressiveness among individuals is associated with polymorphisms in the serotonergic (5-HT) neurotransmitter system. To further investigate the genetics underlying interspecific variation in aggressiveness, 123 wild individuals from five baboon species (Papio papio, P. hamadryas, P. anubis, P. cynocephalus, andP. ursinus ) were screened for two polymorphisms in promoter regions of genes relevant for the 5-HT system (5-HTTLPR andMAOALPR ). Results Surprisingly, despite considerable interspecific variation in aggressiveness, baboons are monomorphic in5-HTTLPR, except forP. hamadryas, which carries one additional allele. Accordingly, this locus cannot be linked to behavioral variation among species. A comparison among 19 papionin species, including nine species of macaques, shows that the most common baboon allele is similar to the one described for Barbary macaques (Macaca sylvanus ), probably representing the ancestral allele in this tribe. It should be noted that (almost) all baboons live in Africa, but withinMacaca onlyM. sylvanus lives on this continent. Baboons are, however, highly polymorphic in the so-called 'warrior gene'MAOALPR, carrying three alleles. Due to considerable variation in allele frequencies among populations of the same species, this genotype cannot be invoked to explain variation in aggressiveness at the species level. Conclusions This study provides another indication that5-HTTLPR is not related to aggressiveness in primatesper se, but may have been under differential selective pressures among taxa and potentially among populations in different geographic regions. The results onMAOALPR alleles inPapio indicate that variation in the metabolism of monoamine neurotransmitters and associated behaviors is more important among populations than among species. We, therefore, propose to compile behavioral data from additional populations ofPapio to obtain further insight into the genetics underlying behavioral differences among primate species.